2020
DOI: 10.1155/2020/9314756
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Low Dose of Lipopolysaccharide Pretreatment on Endotoxin-Induced Uveitis in Rats Is Associated with Downregulation of CSF-1 and Upregulation of LRR-1

Abstract: Purpose. To observe the effect of low dose of lipopolysaccharide (LPS) pretreatment on the expression of CSF-1 and LRR-1 in rats with endotoxin-induced uveitis (EIU), and to explore the possible role of TLR4. Method. EIU was induced by a single subcutaneous injection of 200 μg LPS. For the endotoxin tolerance group, the induction of EIU was preceded by a daily subcutaneous injection of 0.1 mg/kg LPS for five days. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These results suggested that the CSF1/CSF1R axis played a vital role in the pathogenesis of nAMD. A previous study revealed that CSF1 was increased in the iris ciliary body of a rat endotoxin-induced uveitis model, and low-dose lipopolysaccharide pretreatment reduced the expression of CSF1, 29 which indicated that CSF1 acted as an inflammatory cytokine in endotoxin-induced uveitis.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggested that the CSF1/CSF1R axis played a vital role in the pathogenesis of nAMD. A previous study revealed that CSF1 was increased in the iris ciliary body of a rat endotoxin-induced uveitis model, and low-dose lipopolysaccharide pretreatment reduced the expression of CSF1, 29 which indicated that CSF1 acted as an inflammatory cytokine in endotoxin-induced uveitis.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, systemic and cerebral injections of endotoxins such as lipopolysaccharide (LPS) have been shown to promote inflammation and M1 polarization [ 44 , 45 ]. While high doses of LPS are detrimental [ 46 , 47 ], low doses of LPS could be beneficial by causing immunostimulation and alleviating inflammatory response [ 48 , 49 ]. As the blockade of the inflammatory response after UVN was deleterious for both neuroplasticity mechanisms in the deafferented VNs and functional recovery, we wondered whether the slight stimulation of the inflammatory process with low doses of systemic LPS injections could be beneficial for vestibular compensation.…”
Section: Introductionmentioning
confidence: 99%
“…LPS causes several mediators of inflammation to be released, including chemokines and pro-inflammatory cytokines, which ultimately cause cellular damage. 2,3 Toll-like receptor-4 (TLR-4) activated by LPS is known to stimulate Nuclear factor-κB (NFkB) and inhibitor of NF-κB kinase (IKK). Under unstressed conditions, NFkB resides in the cytoplasm together with an inhibitory factor (IκB).…”
Section: Introductionmentioning
confidence: 99%
“…LPS causes several mediators of inflammation to be released, including chemokines and pro-inflammatory cytokines, which ultimately cause cellular damage. 2,3…”
Section: Introductionmentioning
confidence: 99%